Reflexive Sub-Politics in the context of Globalization of Information and the Internet Supranational Regulation - Garcia, Bruna Pinotti (Law, State and Telecommunications Review, 2016)
Purpose ”“ The World Wide Web is emerging not only as a mean of communication but serves as instrumental to the exercise of rights, including participation in sub-politics, so that becomes the interest of the individual put up as participatory actor in the process of discussion of its regulation. In this way, this paper addresses the following research question: Can reflective sub-politics be identified in the comparative scenario of multiple players acting in the regulation of Internet features? Methodology/approach/design ”“ From the outset, the paper earmarks as relevant the understanding of the position of multiple players in the scenario of Internet regulation, which is possible only by supranational law comparative study contextualized with regard to sub-politics. The empirical basis of this paper lies in conferences of the United Nations, the Organization of American States, the European Union and the European Council. Its theoretical basis is focused on Ulrich Beck and Anthony Giddens and the concept of reflexive modernity associated with the policy, forming what is called reflexive sub-politics. Findings ”“ The paper has proved the hypothesis that, regarding regulation of Internet, agendas emerge about Internet regulation that are every step less restricted to the traditional regulatory actors, allowing a greater participation of the individual in this process, with the possibility of designing sub-politics in a more simplified concept of globalization. Practical implications ”“ The article provides to the scientific community and the society cognitive foundations necessary for inclusion of social actors in virtual spaces in the field of supranational regulation of new information technologies. Originality/value ”“ The terms globalization and mundialization have multiple meanings, which does not diminish the importance of understanding them scientifically. It is clear that the phenomenon of mundialization requires the recognition that it should not be perceived as something restricted to the states. The relevance of the subject has not been accompanied by sufficient scientific production in the field.